EFEKTIVITAS PELAYANAN PROGRAM KARTU MACCA DALAM PERATURAN BUPATI NO.23 TAHUN 2016 DI KECAMATAN MARIORIWAWO KABUPATEN SOPPENG PERSPEKTIF SIYASAH SYAR’IYYAH - nur amalia; Akmal, Andi Muhammad (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This study aims to describe the effectiveness of the Macca Card Program Service in Regent Regulation No. 23 of 2016 in Marioriwawo District, Soppeng Regency, Siyasah Syariyyah Perspective. In answering these problems, the author uses a normative syar`i approach and a normative juridical approach. The method of data collection is done by way of interviews, observation, documentation, and literature study. The results of the study show that 1). How the macca card program is implemented during its validity period is not optimal enough in socializing, resulting in a lack of understanding of the community regarding the government program. For employees in implementing it is good enough although it should be further improved 2). This supporting factor is the existence of an adequate budget and the inhibiting factor of this program is the lack of direct socialization to the target beneficiary community. 3). Siyasah Shariyyah's view of the effectiveness of the macca card program service in surah an-nisa verses 58-59 explains that conveying the mandate to those who are entitled to receive it, in this case the government has conveyed the mandate but it is not optimal enough.